A laboratory miniature full-flow penetrometer system for peat - Akeem, Gbenga Amuda; Alsidqi, Hasan; Fauzan, Sahdi; Siti Noor Linda, Taib (ICE Publishing, 2019)
Uncertainties and difficulties surrounding laboratory strength testing of peat have caused the increasing reliance on in situ testing methods, which include T-bar and ball penetrometers, to determine the undrained strength of peat for design purposes. This paper presents the results of miniature full-flow penetrometer (T-bar and ball) tests on decomposed peat samples to provide a better understanding of the interpretation of the strength parameters in this material. The tests were conducted in a pressure chamber, in which miniature T-bar and ball penetrometer tests can be performed on peat samples consolidated under specific vertical effective stresses. Penetrometer bearing factors were derived experimentally using the monotonic penetration resistance and the undrained shear strength estimated from triaxial tests. The bearing factors, expressed as the penetration resistances normalised by the undrained shear strength data (obtained from triaxial tests) compare well with those derived from plasticity solutions. In addition, the remoulded strength parameters derived from penetrometer cyclic tests are comparable with those obtained from fall cone tests. The findings reported in this paper illustrate the capability of full-flow penetrometer tests to measure the undrained strength of peat.